A concepção de Homem no Behaviorismo Radical de Skinner: um compromisso com o bem da cultura - Melo, Camila Muchon de (2004)
B. F. Skinner describes and explains human behavior through the selection by consequences causative model. According to this model, human behavior evolves through interactions among three levels of variability and selection (phylogeny, ontogeny and culture). Three flaws are pointed out by the author in the selection by consequences model. The conception of Man as a cultural planner, suggested in this study, allows the solution of the third flaw . This study had as its aim to investigate Man s conception in Skinner s Radical Behaviorism, derived from his theory on behavior evolution, interpreted as a commitment to the good of the culture. To achieve this, this thesis goes through three aspects: 1st Behavior evolution through the interrelations between survival and reinforcement contingencies; 2nd-Cultures evolution through the interrelations between reinforcement and cultural contingencies; 3rd Man s conception in Skinner s Radical Behaviorism in benefit of the good of the culture.